229| Jurnal Administrasi Bisnis Vol 4 No 3 Juni 2024 Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Divisi Import PT. Monang Sianipar Abadi Kargo (MSA Kargo) - Novianty Santoso, Amelia; Hermawan, Rudianto (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to analyze the influence of leadership and work motivation on the performance of employees in the import division of PT. Monang Sianipar Abadi Kargo. This research uses a quantitative approach. Sampling was conducted using Arikunto's theory (2010:112), which suggests that if the population is small or fewer than 100 people, it is advisable to take the entire population; if the population is large or more than 100 people, a sample of 10-15% or 20-25% or more than 30% can be taken. The sample size for this study is 39 employees in the import division of PT. Monang Sianipar Abadi Kargo. The sampling technique used in this research is non-probability sampling with a saturated sampling (Census) technique. Data testing was conducted using multiple linear regression analysis. The results of this study indicate that leadership and work motivation have a significant and positive effect on the performance of employees in the import division of PT. Monang Sianipar Abadi Kargo (MSA Cargo) simultaneously.